2014
DOI: 10.1155/2014/801346
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Oxidative Stress/Genotoxic Effects Are Related to Serum IgG and IgA Levels in Coke Oven Workers

Abstract: We investigated oxidative stress/genotoxic effects levels, immunoglobulin levels, polycyclic aromatic hydrocarbons (PAHs) levels exposed in 126 coke oven workers and in 78 control subjects, and evaluated the association between oxidative stress/genotoxic effects levels and immunoglobulin levels. Significant differences were observed in biomarkers, including 1-hydroxypyrene levels, employment time, percentages of alcohol drinkers, MDA, 8-OHdG levels, CTL levels and CTM, MN, CA frequency, and IgG, IgA levels bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…o corroborate this hypothesis future experiments with a larger number of animals should be conducted in order to confirm two requirements: (1) if animals with high antibody titres usually have low values of oxidant compounds and also (2) to provide evidence that oxidant compounds compromises antibody function or half-life. Although there are previous studies that described both requirements [ 17 , 47 , 48 ] ideally this should be demonstrated also with the BM95 and BM86 antigens. If this could be demonstrated, vaccine formulations would benefit from producing an antioxidant response able to keep oxidant agents at low concentrations, in order to avoid oxidation of IgG.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…o corroborate this hypothesis future experiments with a larger number of animals should be conducted in order to confirm two requirements: (1) if animals with high antibody titres usually have low values of oxidant compounds and also (2) to provide evidence that oxidant compounds compromises antibody function or half-life. Although there are previous studies that described both requirements [ 17 , 47 , 48 ] ideally this should be demonstrated also with the BM95 and BM86 antigens. If this could be demonstrated, vaccine formulations would benefit from producing an antioxidant response able to keep oxidant agents at low concentrations, in order to avoid oxidation of IgG.…”
Section: Discussionmentioning
confidence: 89%
“…This result could be related to a decrease in protein oxidation and therefore an improvement in the antibody production. High level of oxidants would lead to oxidation and damage of the immunoglobulins [ 17 , 47 ], thus resulting in significant inhibition of antibody activity by altering the secondary or tertiary structure of antibodies [ 19 ]. The lack of changes in FOX could indicate that there is no product of lipid oxidation liberated during the immunization process.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have proven that oxidative stress can cause abnormal levels of immunoglobulins (Nandakumar et al, 2008 ) and reduce the immune function (Srivastava et al, 2017 ). Gao et al ( 2014 ) found that oxidative stress reduced IgA and IgG levels. High levels of HSPs are observed in the process of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The immune mechanisms are implicated in chronic inflammatory response, hypertension, vascular dysfunction and deterioration of organs. [4,5,6] Inflammation is a key feature of atherosclerosis. Elevated levels of white blood cells (eosinophils, monocytes, neutrophils, lymphocytes) and the CRP, the immune responses herald adverse cardiac outcomes, endothelial activation, growth and rupture of the plaque.…”
Section: Introductionmentioning
confidence: 99%